Mortgage enforcement on real estate - Stošić Slobodan (Megatrend Revija, 2015)
In modern economy credit mechanism provides adequate guidance of social wealth. Developed lending involves the construction and establishment of legal principles that would provide additional security to persons who establish mutual credit relationship, which constitutes the rights and obligations. Mortgages as collateral, had a limited scope in countries witch economy is based on strong state intervention in the market. The adoption of new regulations, these institutions again became important and tempting, especially for banks as lenders are all prevalent in the market. If debtor fails to pay its debt when it is due, mortgage creditor can choose between two modes of payment. Mortgage agreement is now enforceable title, by the amendments of executive law. However, after the reform of the judicial system in the Republic of Serbia, courts are still inadequately organized, which is also reflected in the large number of overload of cases, which frustrates the very efficiency of the judicial proceedings for the protection and realization of individual rights.